Amphophilic-vacuolar renal tubule adenoma in a 10-week-old female Sprague– Dawley rat - Lee, Y-H; Kim, T-W; Kim, T-K; Park, H-J; Lee, M-J; Park, S; Im, S; Kim, Y-S (Journal of the Hellenic Veterinary Medical Society, 2025)
Amphophilic-vacuolar (AV) tumors are variants of renal tubule (RT) tumors that showed morphological characteristics that are distinguished from that of the conventional renal tubule tumors. AV tumors are spontaneous, non-treatment-related because of their familial origin, whereas RT tumors are spontaneous or chemically induced. Limited data are available on the occurrence of AV tumors in young Sprague–Dawley (SD) rats. We reported AV RT adenoma in a 10-week-old female SD rat. The affected animal was a 10-week-old female SD rat during a 4-week repeated toxicity experiment. The kidneys of the rat were fixed in 10% neutral buffered formalin, processed routinely, stained with hematoxlin and eosin, and examined microscopically. A small solid mass was accidently found in the cortex of the right kidney of the rat. The mass was well-demarcated and unencapsulated. It had a lobular pattern separated by a thin stand of fibrovascular stroma and was composed of large, round to polyhedral cells, with an amphophilic to lightly eosinophilic cytoplasm, which had large vacuoles, small lumens, and few lymphocytes. Large vesiculated nuclei contained prominent nucleoli. Part of the tumor was compressed from capsule and surrounded by lymphocytic infiltrates. Additionally, a few mitotic figures and apoptotic bodies were observed. This rat was diagnosed with AV RT adenoma on histological findings. AV tumors should be differentiated from RT tumors in toxicity studies because determining whether they are spontaneous or treatment-related, particularly in the highest test-substance dose group, is important. This study provides an example of an AV tumor background in an SD rats.